Peran Supervisor dalam Pengawasan Manajerial dan Faktor-Faktor yang Memengaruhi Kinerja Tenaga Administrasi Sekolah - Dian Ratna Suri (STAIN Bengkalis, 2020)
This article aims to determine the role of supervisors in implementing managerial supervision and the factors that lead to the low performance of school administrative staff at State Junior High School 5 Bantan. This type of research is descriptive qualitative with the subjects of this study are the supervisor, principal, and head of school administration. All data were collected through observation and interviews. The main informants are school supervisors as well as additional informants for school principals and school administration staff. Based on the description of research data, it is known that the role of school supervisors in implementing managerial supervision is quite good, but its implementation is still not maximal in providing direct guidance to administrative staff. Lack of direct coaching by school supervisors, and lack of cooperation between school supervisors and school principals, as well as a lack of professionalism in the performance of administrative staff, are the causes of the low performance of administrative personnel.